Duties and Responsibilities of Midwife Practices in Hazardous and Toxic Waste Management (Case Study Of Lahat Regency) - Shinta Elvira; Eko Nurmadiansyah; Suwandi Sawandi (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Hazardous and toxic waste or what is often called medical waste is waste generated from medical services. The resulting medical waste can endanger public health and have a negative impact on the quality of the environment around hospitals or clinics which can disrupt and cause health problems for people who live in the surrounding environment. One of the places that produce medical waste is the midwife's independent practice. As one independent practice medical waste generators, midwives have an obligation to manage medical waste. This research is a sociological juridical research with analytical descriptive specifications.The data used in this study are primary data which is mainly obtained from interviews and secondary data obtained from literature studies. The data analysis method used is a qualitative method.From the results of the study, it can be seen that in general the independent practice of midwives in Lahat District has managed medical waste by storing and submitting medical waste to medical waste processors. However, from the results of the research, it was found that the management carried out by midwives' independent practice was not in accordance with the Regulation of the Minister of Environment and Forestry Number 56 of 2015 concerning Procedures and Technical Requirements for the Management of Hazardous and Toxic Waste. The absence of medical waste storage and cold storage is one of the obstacles to medical waste management in midwives' independent practice in the Lahat District. The need for regular guidance and supervision on the management of medical waste for health workers to smooth the management of medical waste in Lahat Regency.Keywords: duties, responsibilities, hazardous and toxic waste, medical waste, midwife's independent practice. Abstrak: Limbah bahan berbahaya dan beracun atau yang sering disebut limbah medis adalah limbah yang dihasilkan dari pelayanan medis. Limbah medis yang dihasilkan dapat membahayakan kesehatan masyarakat dan memilik dampak negatif terhadap mutu lingkungan sekitar rumah sakit atau klinik yang dapat menggangu dan menimbulkan masalah kesehatan bagi masyarakat yang tinggal di lingkungan sekitar. Salah satu tempat penghasil limbah medis adalah praktik mandiri bidan. Sebagai salah satu tempat penghasil limbah medis praktik mandiri bidan memiliki kewajiban dalam melakukan pengelolaan limbah medis. Penelitian ini merupakan penelitian yuridis sosiologis dengan spesifikasi deskriptif analitis.Data yang digunakan dalam penelitian adalah data primer yang terutama diperoleh dari hasil wawancara dan data sekunder yang diperoleh dari studi literatur. Metode analisis data yang digunakan adalah metode kualitatif.Dari hasil penelitian dapat diketahui bahwa secara umum praktik mandiri bidan di Kabupaten Lahat telah melakukan pengelolaan limbah medis dengan melukan penyimpanan dan menyerahkan limbah medis ke pengolah limbah medis. namun dari hasil penelitian diketahui bahwa pengelolaan yang dilakukan praktik mandiri bidan belum sesuai dengan Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor 56 Tahun 2015 tentang Tata Cara dan Persyaratan Teknis Pengelolaan Limbah Bahan Berbahaya dan Beracun. Tidak adanya tempat penyimpanan limbah medis dan cold storage menjadi salah satu hambatan pengelolaan limbah medis di praktik mandiri bidan di Kabupaten Lahat. Perlunya pembinaan dan pengawasan yang rutin tentang pengelolaan limbah medis kepada tenaga kesehatan guna kelancaran pengelolaan limbah medis di Kabupaten Lahat.Kata kunci: tugas, tanggungjawab, limbah medis, praktik mandiri bidan.